Optimized dissociation protocol for isolating human glioma stem cells from tumorspheres via fluorescence-activated cell sorting. Issue 1 (10th July 2016) - Lv, Donglai; Ma, Qing-hua; Duan, Jiang-jie; Wu, Hai-bo; Zhao, Xi-long; Yu, Shi-cang; Bian, Xiu-wu
Highlights: This is the first study to optimize the dissociation protocol for isolating human glioma stem cells (GSCs) from tumorspheres. Liberase-TL (200 µg/ml) is an ideal reagent for isolating GSCs from tumorspheres via fluorescence-activated cell sorting. Non-enzymatic cell dissociation solution (NECDS) for such a protocol should be carefully considered. Abstract: Fluorescence-activated cell sorting (FACS) based on the surface marker CD133 is the most common method for isolating glioma stem cells (GSCs) from heterogeneous glioma cell populations. Optimization of this method will have profound implications for the future of GSC research. Five commonly used digestion reagents, Liberase-TL, trypsin, TrypLE, Accutase, and non-enzymatic cell dissociation solution (NECDS), were used to dissociate glioma tumorspheres derived from two primary glioma specimens (091214 and 090116) and the cell lines U87 and T98G. The dissociation time, cell viability, retention of CD133, and stemness capacity were assessed. The results showed that single cells derived from the Liberase-TL (200 µg/ml) group exhibited high viability and less damage to the antigen CD133. However, the efficiency of NECDS for dissociating the tumorspheres into single cells was fairly low. Meanwhile, the use of this digestion reagent resulted in obvious cellular and antigenic impairments. Taken together, Liberase-TL (200 µg/ml) is an ideal reagent for isolating GSCs from tumorspheres. In contrast, the use of NECDS for such a protocol should be carefully considered.